Implementation of Incremental Models on Development of Web-Based Loan Cooperative Applications - Andreansyah, Ahmad; Rachman, Andy; Putri, Rahmi Rizkiana (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2020)
Technology is an integral part of application development. Utilization of technology under the target user application becomes one assessment in the success of a software. The XYZ Savings and Loan Cooperative is a non-bank financial company engaged in savings and loans. In the employee payroll process so far it still uses the manual method, start from recording attendance, up to the salary calculation process. Web-based application development developed by researchers is used to overcome the problems of XYZ Savings and Credit Cooperatives. Development of Savings and Loan Cooperative applications developed using the incremental model. 31 respondents from the company tested the application. Application testing based on usability factor ISO 9126-3. Applications get a value of 82.66% in terms of ease of understanding, 81.50% in terms of ease of study, 81% in terms of ease of operation, 81.33% in terms of interest and 82% in terms of usage compliance. The average total rating in terms of the usefulness of the application get 82.66% so the application is very useful for companies in helping to calculate employee payroll.